KESESUAIAN HABITAT AND EKOLOGI VEKTOR MALARIA DI KALIGESING, PURWOREJO - Hidayati, Fitni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Purworejo is one of the districts in Central Java that established the Malaria Center because it is classified as a malaria endemic area. In malaria control, Village Malaria Technicians (JMD) were formed in each malaria-infected area. Purworejo was supposed to obtain a malaria-free letter at the end of 2021, but cases suddenly spiked in July 2021 to 584 cases. Based on data from the malaria center, the highest cases of malaria were found in the Kaligesing area. The high number of malaria cases in Kaligesing is important to conduct a survey to find out the factors that affect the occurrence of malaria. This study aims to look at malaria risk factors in terms of malaria suitability habitat with measured parameters, namely water temperature, pH, turbidity, Total Dissolved Solid (TDS), and larval density. This research uses an ecological approach with a type of descriptive research using a survey method that can provide an overview of the object being studied. Based on the results of the tests that have been carried out, the highest water temperature was found in Jelok Village (27.7°C), the highest pH in Jelok Village (8.9), the highest level of turbidity was found in Jatirejo Village (8.4 NTU), the highest TDS was found in Kaliharjo Village (389.1 ppm), and the highest larval density was found in Sudorogo Village (4.8 larvae per volume of water).Keywords: Purworejo, Malaria, Habitat suitability, Ecology